THE EFFECT OF INFLUENCER CREDIBILITY AND BRAND FAMILIARITY ON PURCHASE INTENTION THROUGH BRAND TRUST ON THE GLAD2GLOW BRAND ON TIKTOK - Siti Mutmainah; Nur Amalyna Yusrin (STMIK Indonesia Banda Aceh, 2026)
The development of digital marketing has encouraged the use of TikTok influencers as an emerging strategy to promote beauty products and influence consumer decisions. Glad2Glow is one of the brands adopting this approach; however, the extent to which influencer promotions can build consumer trust and shape purchase intention still requires empirical examination. This study examines how influencer credibility and brand familiarity influence consumers’ purchase intention, with brand trust as an intervening variable in the context of Glad2Glow promotions on TikTok. The research employs a quantitative design using data collected through an online survey of active TikTok users. The data were analyzed using structural equation modeling to identify relationships among the constructs and examine mediation effects. The results show that influencer credibility and brand familiarity positively influence brand trust, which in turn strengthens their impact on purchase intention. These findings highlight the important role of trust in influencer-based marketing and provide insights for Glad2Glow in selecting suitable influencers and developing authentic promotional content